Discourse Dimension Analysis of the SK-II #Changedestiny Series Beauty Product Advertisement - Wedayanti, Ni Putu Luhur; Sulatri, Ni Luh Putu Ari (Universitas Muhammadiyah Malang, 2023)
SK-II as an exclusive cosmetic brand from P&G company tries to use social issues about woman’s marginalization as their topics in the commercial theme #changedestiny. This study aims to analyze the advertiser’s real intentions in the text of the SK-II #changedestiny commercial by implementing the three dimensions of critical discourse analysis by Fairclough. The data is collected from the official SK-II and SK-II Indonesia channels on YouTube since they provide qualitative audiovisual data that can be widely accessed and contains creative values. This research uses qualitative analysis methods, by describing the analysis starting from the discussion of the linguistic aspect as a text analysis that finds the repetition of the keyword “change destiny” and the insertion of the word skin in the phrase, becoming “change skin's destiny”. This article found that the #change destiny campaign showed an insistent interest by inserting the word “skin” between the phrase “change destiny”. Although the campaign seems to support the empowerment of women, it also has the main motive to promote its cosmetics which they claim could prevent skin aging. Video ads tend to display implicit recommendations for using their products. The SK-II Change Destiny series advertisement raises social issues that harm women, in the form of video testimonials with a storyline starting from the difficulties faced by women in self-actualization, and ending with success in changing destiny. It is concluded that by showing partiality to women as target consumers, SK-II presents itself as a brand that cares about more than just their consumers’ skin problems, but also the reality that occurs in society, to promote a basis for consumers’ loyalty.